Performance optimisation for dual-hop hybrid FSO/RF system with selection combining - Sharma, Shubha (2020)
This study investigates the performance of a decode-and-forward-relay-based hybrid free space optical (FSO)/radio frequency (RF) system with selection combining. The proposed hybrid system considers an FSO sub-system as a default transmission option and RF sub-system is utilised when FSO is in outage. For the proposed system, the outage threshold signal-to-noise ratio (SNR) is an important parameter and the optimum value for the same has been calculated to achieve the target average symbol error rate (SER) and high capacity. The presented model considers the effect of transmit beam waist, detector size, and jitter variance explicitly for the FSO link. Transmit beam waist and detector size are optimised to minimise the average SER considering various weather conditions and link distances. A unified performance analysis is addressed and exact expressions for outage probability and average SER are obtained. Simple asymptotic expressions are also derived for high SNR to obtain the diversity order. Large coding gains are observed for optimum beam waist compared to any arbitrary beam waist for same average SER. Significant performance improvement is also observed for the proposed system compared to the individual FSO and RF systems. The theoretical and asymptotic analyses are verified by Monte-Carlo simulations.